A randomized controlled trial comparing the effect of conventional and modified handgrip exercise towards the vein size and blood flow of upper limbs in healthy subjects - Kuan, Chooi Lai (2016)
Introduction The rising trend of end-stage renal disease (ESRD) has seen a higher rate of arteriovenous fistula (AVF) creation. Creating a durable vascular access for hemodialysis is a challenge especially in the unfavorable vein size. Smaller vein size (< 2mm) is associated with higher AVF failure rate. Post-operative handgrip exercise had been advocated in ESRD patients and results shown better AVF maturation. We took advantage of this favorable outcome to investigate the effect of handgrip exercise in native vein to explore the potential of implementing pre-operative handgrip exercise as part of the management in ESRD patients. The current study compared the efficacy of two types of handgrip exercises (conventional and modified) in healthy subjects.Method Thirty-two healthy volunteers (11 male, 21 female) were randomized into two types of handgrip exercises. Exercised hand was randomized and the non-exercising hand served as the control. Both interventions followed the same duration (6weeks), same frequency (30min/day) and same intensity (5 sec contraction, 2 sec relaxation), except for the addition of wrist flexion in the modified group. A standardized stress ball was provided to all subjects. Measurements of vessel diameter and blood flow rate done via Doppler ultrasound were taken before and after 6 weeks of exercise. Prior to imaging, subjects were refrained from coffee, alcohol or strenuous activity for 48 hours. The sonography technician who performed Doppler ultrasound imaging was blinded. Results There is no statistically significant difference between conventional and modified handgrip exercise when comparing the vessel diameter and arterial blood flow rate. When compared to their control counterpart, conventional exercise showed significant increment in distal cephalic vein (DCV) (p=0.003) and proximal cephalic vein (PCV) (p<0.001), as well as improvement in brachial artery flow (BAF) rate (p=0.025) but not the modified handgrip exercise. However, the modified handgrip exercise showed a higher percentage of increment in DCV and PCV compared to the conventional group (34.5 vs 27.8%, 26.6 vs 21.1%) although not being statistically significant (p=0.316, p=0.489). Conclusion The conventional handgrip exercise with our proposed protocol could be implemented in ESRD patients before AVF creation. Given the higher percentage of improvement seen in modified handgrip exercise, future investigation is needed to evaluate the outcome of AVF maturation in patients subjected to pre-operative handgrip exercise.